1998
DOI: 10.1093/jac/42.1.75
|View full text |Cite
|
Sign up to set email alerts
|

Gastric mucosal distribution and clinical efficacy of azithromycin in patients with Helicobacter pylori related gastritis

Abstract: The gastric mucosal distribution of azithromycin, the prototype of a new class of macrolide antibiotics named azalides, was studied in patients with duodenal ulcer and Helicobacter pylori-related gastritis. The time course of ulcer healing, H. pylori infection, and gastritis activity was also evaluated. Twenty patients (median age 50 years) received the following treatment for 1 month: three cycles of azithromycin (500 mg/day for 3 consecutive days) on days 1-3, 11-13 and 21-23 plus omeprazole (40 mg/day) for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…However, this association became significant when the use of long-acting macrolides only (azithromycin) was considered in the analysis. Azithromycin is known to achieve high concentrations in the gastric mucus and gastric juice for several weeks after its administration, and this may lead to local subinhibitory concentrations in the vicinity of H pylori which could favour the selection of macrolide-resistant mutants 21 22…”
Section: Discussionmentioning
confidence: 99%
“…However, this association became significant when the use of long-acting macrolides only (azithromycin) was considered in the analysis. Azithromycin is known to achieve high concentrations in the gastric mucus and gastric juice for several weeks after its administration, and this may lead to local subinhibitory concentrations in the vicinity of H pylori which could favour the selection of macrolide-resistant mutants 21 22…”
Section: Discussionmentioning
confidence: 99%
“…Azithromycin is a potentially attractive agent for H. pylori eradication given its excellent inhibitory concentration for this organism and long biologic half-life (4,16) . However, clinical trials with azithromycin have displayed considerable variation with respect to the regimens used and the results obtained.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro, azithromycin is bactericidal against H. pylori. In 1998, a study revealed that azithromycin becomes concentrated in the gastric mucosa in much higher levels than in the plasma (17). The finding supported the hypothesis that azithromycin is an effective antibiotic for treating H. pylori infections (28).…”
Section: Discussionmentioning
confidence: 99%
“…Azithromycin is an azalide similar to clarithromycin but less expensive and less prone to select for resistance (13). Most of the clinical trials examined short-duration azithromycin regimens in treating H. pylori (2–7 days of therapy), which may explain the range of eradication rates observed, from 44% to 93% (17-19). …”
Section: Introductionmentioning
confidence: 99%